GIFTED STUDENTS' PERCEPTIONS ON SCIENCE COURSES IN GENERAL EDUCATION CLASSROOM - Kutlu Abu, Nese; Dal, Elif (Journal of Baltic science education, 2025)
Gifted students often experience different educational needs compared to their peers, especially in subjects like science. The aim of this study was to examine the perceptions of gifted students studying in primary school towards the science course. A phenomenological research method was used. The study group consisted of twenty-four gifted students aged 9–10 years studying in eleven different primary schools in a province in southeastern Türkiye during the 2023-2024 academic year. Data were collected through semi-structured interviews, which were conducted face-to-face. The data were analyzed using content analysis in the MAXQDA 24 software. Gifted students show a strong interest in astronomy, earth sciences, and chemistry, while their interest in other scientific fields, such as biology, is limited. They reported that science lessons often use teacher-centered, text-based approaches that offer limited technology active learning. Although science education at the Science and Art Center was satisfactory, the students expressed that regular classroom practices did not meet their expectations. Students emphasized the need for innovative teaching methods, active learning, laboratory activities, and outdoor learning opportunities. The findings indicate that teaching methods need to be improved, and student-centered approaches can enhance course quality and increase student motivation.